Ecologia funcional e trófica de comunidades de peixes de rios intermitentes do semiárido brasileiro - Silva, Milena Gonçalves da (2023)
Community ecology focuses on species interactions and how they influence the structure and dynamics of communities. Throughout history, debates have arisen between the perspectives of Clements and Gleason regarding community organization, with Clements emphasizing interdependence and Gleason highlighting individual species responses to the environment. The concept of ecological niche has played a crucial role in understanding species-environment interactions, with contributions from Grinnell, Elton, and Hutchinson. Understanding species coexistence has been shaped by the principle of competitive exclusion and the neutral theory of coexistence proposed by Gauze and Hubbell, respectively. The knowledge built in the history of community ecology has contributed to comprehending assembly processes through Diamond's formulation of "assembly rules." Community assembly is a dynamic process occurring across various spatial scales, encompassing patterns and processes studied in ecological research, from smaller scales such as environmental filters, stochastic drift, and interspecific interactions, to larger scales like regional species pools, climate, and dispersal limitations. MacArthur and Wilson's Island Biogeography explores spatial dynamics in assembly, while the metacommunity approach considers interconnections among local communities on a larger regional scale. Recognizing the scale dependence in ecological studies has been pivotal in understanding community processes. In the pursuit of general assembly rules, the functional trait-based approach arises. This approach, grounded in species traits, delves into how physiological-ecological adaptations shape interactions with the environment. Additionally, interactions among organisms, exemplified by food webs, are fundamental for understanding relationships within communities. The environmental context in which species occur significantly influences their interactions, particularly in highly dynamic aquatic environments with severe drying periods. Intermittent rivers, ceasing flow or drying temporally and spatially, are included in these dynamic systems and are projected to increase in number due to climate change in the coming decades. Fish, as prominent components of aquatic ecosystems, serve as models for understanding the impacts of droughts and climate change. Thus, this thesis is divided into two chapters that address the functional structure and predatorprey interaction networks in fish communities, influenced by the hydrological dynamics of intermittent rivers in the Brazilian semiarid region